(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Millions around the planet delve in the internet world for research, finance, retail purchases, banking transactions and what not. However much thought is not given about the legal ramifications involved in these transactions. Most people think internet synonymous with the World Wide Web, but it is not. The Internet is a network of Computer networks. Because the internet is a coalition of networks throughout the world, no one organization owns the Internet. The internet was designed as a collaborative environment and therefore was not a high security environment. Founded by academics the open exchange of information became a basic tenet of the internet. The sudden expansion of World Wide Web commercial usage has raised numerous legal issues regarding privacy, security and copyright and trademark infringement and obscenity.